Створення мережі архівних уст анов на Черкащині у 1919–1937 рр. - Клименко, Т. (Архіви України, 2008)
The article deals with some historical and organization issues of the archives in Cherkasy oblast in 1919 – 1938. The history of archival construction in Cherkasy oblast is directly connected with the establishment of the Soviet power in Ukraine. Activities relating to archives formation in Cherkasy oblast began in 1919. In March, 1919 the Commissariat for National Education of Chercasy oblast adopted the resolution “On Control of Archives, Libraries, Theatres and Cinemas”. At the end of 1919 the House of Culture of Chercasy oblast was opened by the Department for National Education; which included T. Shevchenko

National Museum, the Central National Archives and the Central Library. At that moment it was necessary to concentrate the archives documents of the liquidated former government institutions. Despite painful circumstances of the civil war it was vitally important to rescue valuable historical sources which formed the documentary basis of Cherkasy oblast.